2018
DOI: 10.5455/medscience.2017.06.8728
|View full text |Cite
|
Sign up to set email alerts
|

Multigravidas' perceptions of traumatic childbirth: Its relation to some factors, the effect of previous type of birth and experience

Abstract: To investigate the relationship between multigravidas' perceptions of traumatic childbirth (PTC) and their socio-demographic characteristics and the effect of their previous types of birth and experiences on PTC. This descriptive study was conducted in a state hospital in Northern Turkey. The universe of the study consisted of multigravidas. The sample of the study comprised 161 pregnant women determined with G power analysis. The data were collected using the "Pregnant Introductory Information Form" and "Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
6
25
0
5
Order By: Relevance
“…If the midwives exposed to trauma are not treated, the mental health of the women that these midwives care for is at risk 4 , 11 , 23 . In a qualitative study, non-empathic behaviors, and some applications (such as fundal compression, episiotomy) of midwives 30 and the negative attitude and ability of midwifery in the previous birth of multigravidas in another study 31 were found to have an impact on negative birth experience and traumatic birth perception. However, the midwife’s empathic and emotional relationship with women can reduce the risk of trauma.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…If the midwives exposed to trauma are not treated, the mental health of the women that these midwives care for is at risk 4 , 11 , 23 . In a qualitative study, non-empathic behaviors, and some applications (such as fundal compression, episiotomy) of midwives 30 and the negative attitude and ability of midwifery in the previous birth of multigravidas in another study 31 were found to have an impact on negative birth experience and traumatic birth perception. However, the midwife’s empathic and emotional relationship with women can reduce the risk of trauma.…”
Section: Discussionmentioning
confidence: 97%
“…The legal process after birth trauma can further deteriorate the birth trauma of the midwife 24 , 31 . This study revealed that the midwife’s sadness due to the lawsuit filed against her or her collecting evidence against the possibility of a lawsuit was a further trauma for her.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in their previous vaginal deliveries were compared with women who did not undergo intervention during their deliveries, and traumatic birth perception levels were found to be higher in women who experienced interventional vaginal delivery compared to other women 3,8 . In another study, it was found that women who had a previous vaginal delivery with the help of a midwife and had high birth satisfaction levels were found to have low traumatic birth perception 9 . The results of the research show that the support of the midwife and her communication with pregnant women are very important in determining the traumatic perception of birth 10 .…”
Section: Introductionmentioning
confidence: 87%
“…Several studies investigating the empathic skills of midwives and maternal satisfaction in birth experience suggest that midwives' communication scores are insufficient, 11‐13 the mothers are dissatisfied with their birth experience due to their midwives' negative attitudes and behaviours, 14‐16 and the level of vaginal birth satisfaction is low 9,11,17 . Mother‐friendly hospital practices 18 and childbirth preparation training 19 are some of the practices that aim to improve maternal satisfaction and perception of positive birth at birth.…”
Section: Introductionmentioning
confidence: 99%